Operational Analysis of the Apron Movement Control (AMC) Unit in Handling Aircraft at Abdulrachman Saleh Airport Apron Malang - Wahyu Ashari Tri Gunawan; Rahimudin Rahimudin (CV. Rayyan Dwi Bharata, 2023)
Apron Movement Control (AMC) is an airport personnel who has a license and rating to carry out duties as responsible for flight operations, supervision, aircraft movement, vehicle traffic, passengers and cleanliness supervision in the airside area and records flight data on the apron. Supervision carried out by AMC aims to create flight security and safety and create discipline from service users which can affect activities on the air side. The purpose of this study was to find out how the Apron Movement Control (AMC) Unit Standard Operational Procedure is in handling aircraft on the apron and the obstacles faced by the AMC unit at Abdulrachman Saleh Airport Malang. This research is a qualitative research using primary data and secondary data. Data collection techniques used are observation, interviews and documentation. The observation is to conduct a review or direct observation in the working area of the AMC unit. The interviews in this study were AMC officers consisting of the head of the AMC unit and 2 personnel. The documentation is collecting data at the time of observation and interviews, as well as taking pictures during field activities. The results of this study can be concluded that the Standard Operational Procedure unit Apron Movement Control (AMC) in handling aircraft on the apron, namely service and supervision. Services, namely arranging aircraft movements, plotting parking stands, services for emergency aircraft using follow me vehicles. Then the supervision referred to is supervision of vehicle traffic, movement of people/passengers, loading and unloading of goods, routine inspections of FOD, supervision during refueling, and when the engine is running up. The performance of AMC officers is said to be good because they carry out their duties in accordance with the Standard Operating Procedure (SOP) from the Ministry of Transportation and UPT. Obstacles in operational activities, namely the determination of parking stands still refers to the Indonesian Air Force and radio communications that often break up between ATC and AMC, AMR's accurate data is delayed in entering ATC and GH/airline units, heavy damage to aprons and taxiways, and airlines are late in delivering flights schedule. The solution to this problem is that the AMC unit holds internal and external meetings with ATC, GH and the Indonesian Air Force, so that the three parties can determine the best solution regarding flight operations.